Study of antibacterial performance of a type 304 Cu bearing stainless steel against airborne bacteria in real life environments. (13th April 2015) - Yin, Y.; Zhang, X.; Wang, D.; Nan, L.
Abstract : A type 304 Cu bearing stainless steel (304-Cu SS) possesses broad spectrum antibacterial properties in the laboratory environment. However, multiple bacterial species exist in real life environments, and some can cause severe diseases to humans. Therefore, a study of the antibacterial performance of 304-Cu SS in different real life environments is of importance. In this study, direct plate counting, transmission electron microscopy (TEM), confocal laser scanning microscope and scanning electron microscope (SEM) were used to investigate the antibacterial abilities of 304-Cu SS in three different real life environments, a clean room, a filter mesh in an air conditioning unit and a hand sink. The results showed that, after 24 h exposure to different environments, the antibacterial rates of the 304-Cu SS against planktonic airborne bacteria were 92·1% for the clean room, 85·7% for the filter mesh and 77·8% for the hand sink respectively, and the sessile bacteria from the hand sink and filter mesh adhered readily to the 304 SS. Compared to 304 SS, only a few sessile and planktonic bacteria adhered to the 304-Cu SS, indicating that 304-Cu SS with saturated Cu rich precipitates should possess obvious antibacterial ability against airborne bacteria and effectively inhibit the biofilm formation on its surface. In the clean room, only some planktonic airborne bacteria appeared on the surface of both steels. These results provided experimental evidence for practical applications of the 304-Cu SS in different real life environments.